1994
DOI: 10.1007/bf01540983
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an abnormal profile of interleukin-4 (IL-4), IL-5, and ?-interferon (?-IFN) in peripheral blood T cells from patients with allergic eosinophilic gastroenteritis

Abstract: Allergic eosinophilic gastroenteritis is characterized by elevated total IgE, specific IgE to food antigens, and eosinophilia of tissue and blood. Because the lymphokines IL-4, IL-5, and gamma-interferon, regulate IgE synthesis, and eosinophilopoiesis in vitro, we examined whether there is an imbalance in their production in allergic eosinophilic gastroenteritis. To explore this hypothesis, three adult patients with allergic eosinophilic gastroenteritis were studied. Flow cytometric studies of peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 42 publications
0
47
0
3
Order By: Relevance
“…41 In clinical studies, increased secretion of IL-4 and IL-5 by peripheral blood T cells has been reported in patients with EG. 54 Furthermore, T cells derived from the lamina propria of the duodenum of patients with EG preferentially secrete Th-2 cytokines (especially IL-13) when stimulated with milk proteins. 55…”
Section: The Allergic Mechanismmentioning
confidence: 99%
“…41 In clinical studies, increased secretion of IL-4 and IL-5 by peripheral blood T cells has been reported in patients with EG. 54 Furthermore, T cells derived from the lamina propria of the duodenum of patients with EG preferentially secrete Th-2 cytokines (especially IL-13) when stimulated with milk proteins. 55…”
Section: The Allergic Mechanismmentioning
confidence: 99%
“…As such, the diagnosis of eosinophilic gastritis (EG), enteritis, and gastroenteritis is even more complex than EE. Although these diseases are idiopathic, an allergic mechanism has been suggested in at least a subset of patients [26]. Indeed, elevated total IgE and food-specific IgE have been detected in most patients.…”
Section: Eosinophil-associated Small Bowel Disordersmentioning
confidence: 99%
“…Todavia, embora a absorção de macromoléculas seja elevada em prematuros, isso não está necessariamente associado a maior incidência da AA 2,16 . 19,20 . Contudo, essas informações vêm sendo pouco usadas para desenvolver abordagens clínicas mais específi-cas ou sensíveis para o diagnóstico e manejo da AA.…”
Section: Patogêneseunclassified